Փոքրաչափ համապիտանի կերամանրիչի մշակում և շահագործական ցուցանիշների որոշում - Մարգարյան, Ստեփան; Մարգարյան, Արմեն; Մազմանյան, Արամ; Պապյան, Սերյոժա (ՀԱԱՀ հիմնադրամ)
Известно, что кормление животных измельченными кормами (концентрированными, грубыми и сочными) способствует повышению их переваримости и уменьшению кормовых потерь. Измельчение кормов достаточно трудоемкий процесс, поэтому важна его механизация. Изучив устройство и принцип работы используемых в производстве кормоизмельчителей и выявив их недостатки, мы разработали и испытали малогабаритный универсальный измельчитель кормов (патент РА N 906Y). Полученными в результате научных экспериментов эксплуатационными показателями измельчителя нами обосновано, что он может использоваться в фермерских хозяйствах для одновременного измельчения зерновых, грубых и сочных кормов. Feeding animals with crushed feed (such as grain, coarse, and succulent feeds) enhances digestibility and reduces feed losses. The process of crushing feed is labor-intensive, and its mechanization is crucial for efficiency. Currently, there is a growing demand for compact equipment capable of efficiently crushing various types of feed. Existing feed grinders often suffer from low productivity, high energy consumption, excessive wear on metal components, and the inability to process different types of feed without changing working parts depending on the feed’s characteristics. To address these limitations, a prototype of a compact, universal feed grinder (model AP N 906Y) was developed. This grinder can simultaneously process grain, coarse and succulent feeds of varying moisture and hardness, making it suitable for use on farms. Based on experimental testing, key kinematic parameters and operational indexes were determined. The small-sized universal feed grinder is compact, easy to operate, and features a simple design. Its key advantages include: The ability to simultaneously chop two different types of feed. Adjustable working part speeds. Use of wider working parts, eliminating the need to dismantle and reassemble components for different feed types. The grinder offers high productivity, low metal consumption, reduced energy and labor costs, and is easy to maintain, making it a practical solution for modern feed processing needs.
Keywords: Ագրարային ճարտարագիտություն